2017
DOI: 10.1371/journal.pone.0173777
|View full text |Cite
|
Sign up to set email alerts
|

Improved costs and outcomes with conscious sedation vs general anesthesia in TAVR patients: Time to wake up?

Abstract: BackgroundTranscatheter aortic valve replacement (TAVR) has become a commonplace procedure for the treatment of aortic stenosis in higher risk surgical patients. With the high cost and steadily increasing number of patients receiving TAVR, emphasis has been placed on optimizing outcomes as well as resource utilization. Recently, studies have demonstrated the feasibility of conscious sedation in lieu of general anesthesia for TAVR. This study aimed to investigate the clinical as well as cost outcomes associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 14 publications
3
49
0
1
Order By: Relevance
“…17 LA/CS was shown to achieve greater improvement of patient's quality of life at 30 days post-TAVR, as assessed by Kansas City Cardiomyopathy Questionnaire compared with general anesthesia. 12 Additionally, for elderly patients, shorter LOS is beneficial, considering the potential reduction in known negative outcomes of longer hospitalization, including reduced functional status, infection, or delirium. 18 There is also lower 1-year mortality rates among patients with severe chronic obstructive pulmonary disease undergoing minimalist approach when compared to the standard procedure.…”
Section: Minimalist Transcatheter Aortic Valve Replacement: Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…17 LA/CS was shown to achieve greater improvement of patient's quality of life at 30 days post-TAVR, as assessed by Kansas City Cardiomyopathy Questionnaire compared with general anesthesia. 12 Additionally, for elderly patients, shorter LOS is beneficial, considering the potential reduction in known negative outcomes of longer hospitalization, including reduced functional status, infection, or delirium. 18 There is also lower 1-year mortality rates among patients with severe chronic obstructive pulmonary disease undergoing minimalist approach when compared to the standard procedure.…”
Section: Minimalist Transcatheter Aortic Valve Replacement: Potentialmentioning
confidence: 99%
“…21,26 LA/CS were associated with lower rates of systemic hypertension and subsequent intra and post-procedural inotropic support, and potentially lower pulmonary complications rate, like the incidence of respiratory failure and pneumonia associated with mechanical ventilation. 22,23 As a result, early recovery after the procedure can be achieved, leading to a shorter length of post-procedural ICU stay and LOS, 12,20,22,25,27 e.g. mean 1.5-2.1 days shorter in LOS under LA/CS than under general anesthesia.…”
Section: Local Anesthesia/conscious Sedationmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies of the standard and minimalist approaches indicate that in the current era, given the advent of smaller-sized sheaths and valve profiles, the minimalist transfemoral approach can be performed with minimal morbidity and mortality and equivalent effectiveness compared with the standard approach (33,34). Furthermore, a shorter length of hospital stay and lower resource use with the latter approach significantly lowers hospital costs.…”
Section: Minimalistic Approachmentioning
confidence: 99%
“…Results are expressed as Mantel Haenszel Risk Ratio (RR) or mean difference (MD) with 95% confidence intervals (CI) [1]. In addition to the 26 studies included in our previous analysis, we found 6 new studies (with 12,453 patients) meeting our inclusion criteria [2][3][4][5][6][7].…”
mentioning
confidence: 99%